Perspectives on the role of Cultural Heritage Tourism in community development in South Africa: a study of Mapungubwe World Heritage Site in Limpopo Province - Shabalala, Lombuso Precious (My University, 2020)
Today, a World Heritage status enhances the value of a tourist site and is a marker of the authenticity of the site in terms of its cultural heritage. South Africa is home to ten declared World Heritage Sites (WHSs) which are expected to lead to the economic development associated with tourism products and services, contributing to improving the standards of living of the local people. At the same hand, tourism is perceived to be the most powerful economic, social, cultural, ecological and political forces in the world today. However, benefits to local communities and heritage custodians’ from cultural heritage tourism in heritage sites remains a concern, including the realisation of social and economic development in its true sense. This study examined perspectives on the role of cultural heritage tourism in community development in South Africa, using the Mapungubwe World Cultural Heritage Site (MWCHS) as a case study. The South African government has put in place a National Tourism Sector Strategy focusing on harnessing and aligning the strengths of the public and private sectors to ensure the optimal use of resources, as well as . Therefore, community support and involvement on how the past is presented, as well as understanding the economic impact of the tourism industry, becomes paramount for any heritage tourism project or activity. A combination of positivist and social constructivist philosophies (Critical Theory, Basic Needs Theory and Complexity Theory) were deployed as analytical approaches in this study. These theories provided an approach that acknowledges and embraces the complex systems thinking benefits that can be identified and solutions that can address the complex challenges facing the Mapungubwe WCHS, local communities and their descendants. A sequential mixed-method of data collection was adopted for this research. Explanatory semi-structured interviews were conducted in the first stage of fieldwork before the administration of survey questionnaires in stage two. Both qualitative and quantitative data collection methods were used to answer the research questions and meet the research objectives. In terms of sampling, the target populations are the local community, descendants of Mapungubwe and local farmers including Mmanagement and staff of the Mapungubwe WHS. The target population included the South African National Parkss head office representatives from its tourism and development units in Pretoria. A non-probability purposive sampling technique was adopted for both the questionnaire survey and semi-structured interviews. Content analysis (thematic and descriptive in nature) was performed on the qualitative data and Statistical Package for the Social Sciences (SPSS) was used to analyse the quantitative data. Findings were presented in the form of tables, graphs, texts and excerpts. The key finding established that the participants reported not to have benefited from the Mapungubwe WCHS. They also reported not being engaged or not participating in any activities taking place on the site. By contrast, the participants who reported that they were engaged and also participated in activities, also reported to have benefitted from the site. This finding proved that a correlation exists between community engagement, community participation and benefiting from the proceeds derived from site. This mean participation in activities that are taking place in the Site have a direct influence towards benefiting. When there is no community participation there will be no community beneficiation. In addition, the finding also suggests a lack of consistency in community engagement, lack of presentation and fair distribution of meaningful roles, which talks diretly to transparency and effective leadership. Drawing from the findings, this study has developed a conceptual Stakeholders Participation Model aimed at assisting with the establishment of a stakeholders ’participation in MWCHS. This model can be applicable to any WHSs that share similar characteristics as MWCHS. The model appreciate effective leadership and transparency by management including active participation of stakeholders in MWCHS. It envisaged that the model will help to address the challenges posed by the focus groups on dealing with local communities and descendants’ communities. Lastly, the World Heritage Committee of UNESCO has emphasised the need to improve the role of communities at all levels in the identification, protection and management of World Heritage sites. In addition, the heritage that exists in these sites belong to the local community (descendants of the site) and it is marketed to the world under the cultural heritage tourism umbrella. Therefore, it will be a good gesture for local communities or descendants to also benefit from the proceeds gained from these sites
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, Faculty of Science at the University of the Witwatersrand, 2020